Social Skills of Elementary School Students in Bandung-West Java - Irfan Fauzi; Ahman; Syamsu Yusuf; Jiraporn Chano (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
The article aimed to identify the social skills aspects of elementary school students in Bandung. The research method used a survey using the social skills improvement system instrument that developed by Gresham & Elliott. This research was conducted on students in grades 4, 5, and 6 in Bandung, West Java with a total of 343 students. The data collection technique used a survey, and the analysis used descriptive statistics by calculating the percentage of each aspect of social skills. Then it categorized the percentage based on criteria, namely very high, high, low and very low. The results of this research showed that the social skills achievements of elementary school students in Bandung were in the high category with an average percentage of 78.15%. The aspect of social skills that has the highest achievement was responsibility, the very high category with an average percentage of 84.06%, and the aspect of social skills that has the lowest achievement was self-control, the high category with an average percentage of 69.68%. This research contributed of education in understanding various aspects of social development, especially on the social skills of elementary school students. This research was the basis for the development of programs or interventions to improve social skills through various activities relevant to elementary school students.